Silver porous nanotube built three-dimensional films with structural tunability based on the nanofiber template-plasma etching strategy - He, Hui (Langmuir : the ACS journal of surfaces and colloids, 2011)
A facile and high-throughput strategy is presented to fabricate three-dimensional (3D) hierarchically porous Ag films, with clean surfaces, via plasma etching Ag-coated electrospun nanofiber template. The films are built of Ag porous nanotubes and are homogeneous in macro-size but rough and porous in nanoscale. Each nanotube-block is micro/nanostructured with evenly distributed nanopores on the tube walls. The film architecture (or the shape, arrangement, and distribution density of porous nanotubes; the number and size of nanopores) can be easily controlled by the nanofiber-template configuration, Ag coating, and plasma etching conditions. Such hierarchically porous films could be very useful, such as in catalysis, sensors, and nanodevices. They have exhibited significantly structurally enhanced surface-enhanced Raman scattering performance with good stability and reproduction, and shown the possibility of molecule-level detection. Also, the strategy is universal for fabricating other hierarchically structured 3D metal porous films, such as porous Ag hollow sphere arrays